PROCESSING AND CHARACTERIZATION OF OIL PALM LOOSE FRUITS AS A RAW MATERIAL FOR BIODIESEL - Prihatiningtyas, Indah; Heryadi, Eko; Ramadhan, Ridho; Purnomo, Agus; Alfiyya, Alfiyya; Abdullah, Hilham (FKIP USK, 2024)
The main product of oil palm plantations is oil palm fresh fruit bunches, however there is oil palm loose fruits which is detached from the ripe fresh fruit bunch or found during the process of cutting at harvest. Biodiesel could be obtained by processing crude palm oil (CPO) with trans-esterification process, however CPO is an important source of food, especially for cooking oil. Biodiesel production as a source of new renewable energy increases, hence it could threat the food security programs. The oil palm loose fruits as an industrial waste were investigated for renewable energy sources to overcome the conflict between the renewable energy program and food security. This research found that oil palm loose fruits consisted about 55% of mesocarp (flesh of fruit) and around 45% of the seed. Increasing delay on processing of oil palm loose fruits led to decreasing of the oil, and processing delay for 12 days resulted in a significant reduction extract yield. Increasing processing delay reduced the iodine value and the study showed that oil palm loose fruits after 12 days have a high level of oil saturation and free fatty acid of CPO was 37%. Esterification followed by transesterification was conducted to synthesis biodiesel. The biodiesel was obtained with yield of 14.5%, and free fatty acid of 1.3%, while fatty acid methyl ester was achieved 70.24%. Hence, we could convert oil palm loose fruits into biodiesel as a strategy to meet the renewable energy requirement produced from non-food crops